Placental cyst – case study - Murlewska, Julia; Respondek-Liberska, Maria; Lusińska, Agata; Poszwa, Przemysław; Sajdak, Stefan (Prenatal Cardiology, 2019)
We present a case of a large and growing protruded subchorionic placental cyst noted during routine ultrasound evaluation at 25.6 weeks in a pregnant woman with polycystic ovary syndrome (PCOS) and simple left ovarian cyst. We observed evidence of progressive and persisted be weekly repeated reduction of fetal cerebral-placental blood flow. Prenatal ultrasound evaluation, including detailed fetal echocardiography, allowed for safe pregnancy continuation and avoidance of the prematurity. Wide placental infarction, fibrin exudation, decalcifications, and severe disturbances in fetal and maternal circulation were reported based on pathologic postnatal evaluation.